Potoczna onimia poznańska w świadomości mieszkańców miasta - Piotrowicz, Anna; Witaszek-Samborska, Małgorzata; Walczak, Bogdan (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2013)
The article, which analyses material acquired through poll collection, focuses on the awareness of inhabitants of Poznań (aged 35 to 85) of colloquial urban onymes, and is related to an earlier text by the authors, which presented results of the same poll among students of the Faculty of Polish. It turned out that commonly known and used names constitute almost half of the onymes listed in the poll (Akumulatory, Bema, Botanik, Ceglorz, Chwiałka, Dąbrówka, Deptak, Krzyże, Kupiec, Marcin, Marcinek, Okrąglak, Paderek, Pigalak, Raczyńscy, Raszeja, Struś, Szamarzewo, Teatralka). The stability of urban onymy in the language of inhabitants of Poznań is confirmed by phenomena such as: 1) transfer of names on new urban objects (Adaś, Akwarium, Ceglorz, Gargamel, Kanty, Krzyże, Młyn, Paderek, Szamarzewo, Teatralka); 2) extension of referentiality of names because of changes in extralinguistic reality (Chwiałka, Dąbrówka, Marcinek); or 3) creation of new urban onymes (Bulaj, Cyryl, Biblia), including derivates (Bema – Bemowo, Chwiałka – Chwiała).